Amelioration of glucose intolerance through directly acting antiviral agents in chronic hepatitis C cirrhotic patients without overt diabetes. Issue 9 (7th June 2022) - Jang, Tyng‐Yuan; Lin, Yi‐Hung; Liang, Po‐Cheng; Yeh, Ming‐Lun; Huang, Ching‐I; Liu, Ta‐Wei; Wei, Yu‐Ju; Hsu, Po‐Yao; Yang, Jeng‐Fu; Hou, Nai‐Jen; Wang, Chih‐Wen; Hsieh, Ming‐Yen; et al.
Abstract: Hepatitis C virus (HCV) eradication through antivirals ameliorates metabolic profiles. The changes in 2‐h plasma glucose (2HPG) levels by oral glucose tolerance test (OGTT), in chronic hepatitis C (CHC) patients who receive directly acting antivirals (DAAs) was elusive. Five hundred and thirty‐three CHC patients who achieved sustained virological response (SVR, undetectable HCV RNA throughout 3 months after the end‐of‐treatment) by DAAs were consecutively enrolled. Pre‐ and posttreatment 2HPG levels and glucose status were compared. The proportion of patients with improved, worsened, and stable 2HPG was 14.4% ( n  = 77), 18.6% ( n  = 99), and 67.0% ( n  = 357), respectively. Compared with patients with worsening 2HPG, those with improved 2HPG had a higher proportion of cirrhosis (45.5% vs. 24.2%, p  = 0.004) and higher pretreatment 2HPG levels (175.3 vs. 129.5 mg/dl, p  < 0.001). High baseline 2HPG was independently associated with improved 2HPG in multivariate analysis (odds ratio [OR]/CI: 1.05/1.03–1.06, p  < 0.001). When baseline 2HPG was not taken into account, cirrhosis was the only factor independently associated with improved 2HPG status (OR/CI: 2.58/1.29–5.15, p  = 0.007). Linear regression analysis revealed that factors independently correlated to changes in 2HPG levels were female sex (β: 8.78; 95% CI:2.34, 15.22; p  = 0.01), diabetes (β: −27.72; 95% CI: −50.16, −5.28; p  = 0.02), liver cirrhosis (β: −8.91; 95% CI: −16.75, −2.20; p  = 0.01), and genotype 1 of HCV (β: −0.12; 95% CI: −15.19, −2.43; p  = 0.01). 2HPG improved after HCV eradication by DAAs, particularly in cirrhotic patients.